The Profile of Principals’ Instructional Leadership in Primary Schools with High, Moderate, and Low Achievement - Dwi Esti Andriani; Rosa Dania; Suyud Suyud; Setya Raharja; Devi Monita Kristyningsih (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2022)
This study aims to examine 1) the profiles of the principal instructional leadership in three different school categories, namely high, moderate, and low-performing public primary schools: and 2) the differences of, if any, principal instructional leadership in those three different school categories. This was a descriptive study. The respondents were 233 classroom teachers, from 10 selected public primary schools in Bandung District, West Java, Indonesia. They were required to fill up a questionnaire in which they assess the instructional leadership behaviors of their principal. The questionnaire was tested for its validity and reliability before being distributed to the respondents. The collected data was then analyzed using quantitative data analysis techniques. The results show that theprofiles of principal instructional leadership in the three different school categories were relatively similar, viewed from the aspects of determining the school missions focusing on academic achievement, managing teaching programs, and developing a positive learning climate. Of those three dimensions, determining school missions was the most prominent. Looking at more details, supervising and monitoring students#39; learning, managing effective learning hours, and maintaininghigh visibility were the least performed. Finally, this study found that there was no behavioral difference in the principal instructional leadership in the three school categories